IMMUNE RESISTANCE VIA A PD-1/PD-L1 MECHANISM IN GLIOBLASTOMA - V.S. KUSHNIROVA; S.S. SKLYAR; K.A. SAMOCHERNYKH; A.P. TRASHKOV; B.I. SAFAROV (Avicenna Tajik State Medical University, 2023)
Immunotherapy is a treatment option that is becoming more common for different types of cancer. The idea behind this therapy is to modify the patient's immune system. One type of this therapy involves blocking the binding between PD-1 and PD-L1. By doing so, it enables increased antitumor immune activity. Immune checkpoint inhibitors have shown significant efficacy with high response rates and long-term remission in various types of cancer. Glioblastoma (GBM) is a recurrent tumor characterized by immune evasion mechanisms that resist modern immunotherapy. The literature review analyzed the mechanism of tumor resistance to immune response, specifically PD-1 and PD-L1 expression in GBM. The review presented several clinical studies that showed the results of using immune checkpoint inhibitors in GBM patients. Additionally, the review described other mechanisms of tumor resistance to the activated immune system. All sources were selected using specialized scientific retrieval systems and full-text databases such as Google Scholar, eLIBRARY, PubMed, and Elsevier.